Proceso atención de enfermería en escolar con linfadenitis aguda en cara y cuello. - Villalta Bajaña, Solange Polet (2024)
Acute lymphadenitis is an inflammation of the lymph nodes commonly caused by bacterial, viral, or, less frequently, fungal infections. In pediatric patients, this condition typically presents in the cervical region, including the submandibular area, with swollen and painful nodes, often accompanied by fever. Clinical management focuses on identifying the pathogen, administering appropriate antibiotic treatment, and managing symptoms. Differential diagnosis is crucial to rule out more severe conditions and ensure effective treatment. This study aims to detail the nursing care process in managing acute lymphadenitis, covering from admission to patient recovery. reatment, which included antibiotics and antipyretics, led to satisfactory recovery without the need for surgical intervention. Continuous care and family education were essential for treatment success and complication prevention. The case underscores the importance of immediate and adequate medical and nursing care in lymph node infections in pediatric patients. It highlights the critical role of clinical assessment, symptom management, and caregiver education, utilizing an integrative approach based on NANDA, NIC, and NOC to ensure comprehensive and effective care.